Criminal Offence of Online Gambling: An Indonesian Criminal Law Perspective - Reni Purba; Maryano Maryano; Supot Rattanapun (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
This research aims to analyse the criminal act of online gambling in the perspective of criminal law in Indonesia, focusing on the existing law enforcement mechanisms as well as the challenges faced in eradicating online gambling practices. Although Indonesia has clear regulations related to online gambling, such as those contained in the Criminal Code (KUHP) and the ITE Law, this research found that the implementation of law enforcement still faces major obstacles, especially related to the development of information technology, the accessibility of illegal gambling sites, and problems in proving in court. More effective law enforcement requires the integration of more sophisticated technology, cross-border co-operation, as well as a preventive approach to raise public awareness. This research is expected to provide insights for policy makers, legal practitioners, and the public in addressing the problem of online gambling.